Serum lipid and lipoprotein levels of middle-aged and elderly Chinese men and women in Shandong Province - Wang, Meijian (Lipids Health Dis, 2019)
BACKGROUND: Cardiovascular and cerebrovascular diseases have become leading causes of death in China as the economy develop and lifestyles change. This study aimed to estimate the relationship of the age, gender, and glucose metabolism with the serum lipid and lipoprotein levels of middle-aged and elderly Chinese men and women in Shandong Province. METHODS: We conducted a cross-sectional study in Shandong Province that included 10,028 adults aged ≥40 years. Fasting serum total, low-density lipoprotein (LDL), high-density lipoprotein (HDL) cholesterol and triglycerides were measured by standard methods. RESULTS: The estimates of total, LDL, and HDL cholesterol and triglycerides were as follows: 5.35, 3.18, 1.51, and 1.34 mmol/L in the middle-aged and elderly Chinese adult population; 5.14, 3.08, 1.42, and 1.33 mmol/L in male subjects; 5.46, 3.24, 1.56, and 1.34 mmol/L in females; 5.27, 3.11, 1.54, and 1.24 mmol/L in the normal glucose tolerance population, 5.49, 3.27, 1.50, and 1.41 mmol/L in the population with pre-diabetes, and 5.39, 3.23, 1.43, and 1.58 mmol/L in the population with diabetes, respectively. Moreover, 36.92 and 19.10% of the adults had borderline-high and high total cholesterol. The population estimates for borderline-high, high LDL and low HDL cholesterol levels were 25.24, 13.39, and 5.64%, respectively. Meanwhile, borderline high and high triglyceride levels accounted for 16.7 and 17.47% of the population, respectively. CONCLUSIONS: Serum total and LDL cholesterol levels were high in the ≥40 years old population of Shandong Province. Age, gender, glucose metabolism status, body mass index (BMI) and glycosylated hemoglobin (HbA1c) can affect serum lipid and lipoprotein levels.